2009
DOI: 10.1007/s12088-009-0011-3
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of native Bacillus thuringiensis strains by PCR-RAPD based fingerprinting

Abstract: Seventy isolates of Bacillus thuringiensis were isolated from soil samples collected from cotton fi elds. These isolates were characterized by randomly amplifi ed poylmorphic DNA (RAPD) markers to determine their genetic diversity pattern based on their source of origin. Different random decamer primers were used for RAPD amplifi cation, which generated a total of 1935 fragments; of these 1865 were polymorphic and 68 monomorphic. The primers OPA03, OPA08, OPD14, OPD19, OPD20, OPE17 and OPD19 produced 100% poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Vilas-Boas and Lemos (2004) also observed remarkable genetic diversity among 218 Bt isolates from Brazil, suggesing that the diversity resulted from the infl uence of different ecological factors and spatial separation between strains generated by conquest of different habitats. Kumar et al (2008) have also carried out RAPD-PCR of 70 Bt isolates collected from soil samples of a water fi eld and found that RAPD provides a high degree of discrimination.…”
Section: Discussionmentioning
confidence: 99%
“…Vilas-Boas and Lemos (2004) also observed remarkable genetic diversity among 218 Bt isolates from Brazil, suggesing that the diversity resulted from the infl uence of different ecological factors and spatial separation between strains generated by conquest of different habitats. Kumar et al (2008) have also carried out RAPD-PCR of 70 Bt isolates collected from soil samples of a water fi eld and found that RAPD provides a high degree of discrimination.…”
Section: Discussionmentioning
confidence: 99%
“…The results are consistent with the findings of Wei et al (2019) [ 16 ], showing the high specificity of XRE primers for identifying B. thuringiensis . Moreover, it has been well-documented that B. thuringiensis selectively produces insecticidal crystal proteins [ 16 , 23 ], which can be utilized as an appropriate marker for proper identification. Herein, we examined the presence of crystal proteins using crystal protein staining and observed the presence of these crystal proteins in isolate D-1 ( Figure 6 ).…”
Section: Resultsmentioning
confidence: 99%
“…PFGE is generally considered as an accurate and reproducible method for typing clinically relevant bacteria, and has been used for typing Bt strains [ 26 , 30 ]. Another typing method, RAPD, which is fast and simple, also has been applied for the discrimination of Bt strains [ 13 ]. Although RAPD has been successfully used for the differentiation of Bt isolates based on their location of origin, further investigation is still needed to understand their insecticidal spectrum [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another typing method, RAPD, which is fast and simple, also has been applied for the discrimination of Bt strains [ 13 ]. Although RAPD has been successfully used for the differentiation of Bt isolates based on their location of origin, further investigation is still needed to understand their insecticidal spectrum [ 13 ]. For PFGE, it has been reported that the clonal structure of Bt isolates determined by PFGE may not correlate with their cry gene content [ 10 ], however, different conclusions have been made by Gaviria Rivera and Priest [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation